EDUCATION FINANCING MANAGEMENT GOVERNANCE AS AN EFFORT TO IMPROVE FACILITIES AND INFRASTRUCTURE AT MIS AL-KHAIRIYAH WARINGIN SARI TIMUR - Rohman, Jumadi; Hananto, Sigit; Murtafiah, Nurul Hidayati (STIT AL MULTAZAM, 2023)
This study aims to determine the management of education financing in relation to efforts to improve educational facilities and infrastructure at MIS AL-KHAIRIYAH Waringin Sari Timur. The research was conducted using a qualitative case study type approach. The use of this method involves informants who are leaders and structural members of the MIS. The data collection techniques used in this study were observation and interviews with the analytical techniques used, namely data reduction, data display, and verification. The results of the study show that education financing management at MIS AL-KHAIRIYAH Waringin Sari Timur has a family principle, is effective, efficient, productive, transparent and can be accounted for in accordance with existing procedures, namely with a hierarchical pattern up and down to the Chairperson of the Foundation and the community. In improving the quality of education the head of MIS AL-KHAIRIYAH Waringin Sari Timur is in charge of managing education as best as possible and reporting the draft school financing budget is given to the Chairperson of the Foundation, the head of MIS AL-KHAIRIYAH also has the task of how to improve educational facilities and infrastructure at MIS AL-KHAIRIYAH with education financing management by coordinating every activity to colleagues for the realization of quality education through education financing management.